2009
DOI: 10.1038/ijir.2009.8
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between body fat mass and erectile dysfunction in Korean men: Hallym Aging Study

Abstract: The aim of this study was to assess the relationship between body fat mass (BFM) and erectile dysfunction (ED) in Korean men. This study was a cross-sectional study using data on 208 men (the mean age ¼ 67.4 ± 8.2). ED was diagnosed by the International Index of Erectile Function (IIEF)-5 and body fat percentage (BF%) was quantified with bioelectrical impedance. BF% was divided into quintiles (quintile 1: p20.5%, quintile 2: 20.6-23.2%, quintile 3: 23.3-25.8%, quintile 4: 25.9-28.8%, quintile 5: X28.9%). Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
1
18
2
Order By: Relevance
“…In turn, significant correlations were found between the above mentioned sexual parameters and BMI or WHR. The results of our study are in agreement with other studies on cohorts of older men showing that several measures of obesity and central adiposity are significantly associated with ED prevalence [8,[41][42][43]. Orgasmic function was not correlated with any studied parameters.…”
Section: Sexual Fantasiessupporting
confidence: 83%
“…In turn, significant correlations were found between the above mentioned sexual parameters and BMI or WHR. The results of our study are in agreement with other studies on cohorts of older men showing that several measures of obesity and central adiposity are significantly associated with ED prevalence [8,[41][42][43]. Orgasmic function was not correlated with any studied parameters.…”
Section: Sexual Fantasiessupporting
confidence: 83%
“…Details of the HAS have been published elsewhere [21-24]. The first wave began in 2003 and an in-depth clinical study was started in 2004.…”
Section: Methodsmentioning
confidence: 99%
“…Endothelial dysfunction causes impaired arteriolar smooth muscle relaxation, preventing vasodilatation and leading to the development of ED . One small study in Asian men showed that body fat percentage measured using bioelectrical impedance (BIA) had a U‐shaped association with ED, with the highest prevalence of ED in men in the lowest and highest quintiles of body fat percentage …”
mentioning
confidence: 99%